Relationship Analysis of Corporate Governance, Corporate Social Responsibility Disclosure and Economic Consequences: Empirical Study of Indonesia Capital Market - Hapsoro, Dody; Fadhilla, Anna Fauzia (UI Scholars Hub, 2017)
The objective of this study is to investigate the relationship between corporate governance (CG), corporate social responsibility (CSR) disclosure, and economic consequences. Broadly speaking, the CG variables consist of ownership structure and management/control structure. The CSR disclosure variables consist of economic, environmental, social, human rights, societal, and product responsibility dimensions. The economic consequences variables consist of bid-ask spreads, trading volume, and share price volatility. The hypotheses are tested using a structural equation modeling analysis with 210 samples of listed firms on the Indonesian Stock Exchange in 2014. The result of this study is as follows: (1) the effect of the proportion of board of directors from the board of commissioners and the audit committee on the CSR disclosure is positive and significant; (2) the effect of the proportion of independent commissioners and the audit committee from the board of commissioners, the audit committee, and the board of directors on CSR disclosure is positive and significant; and (3) the effect of CSR disclosure on trading volume is positive and significant. The main implication of this study is that CSR disclosure activities have a very important role in meeting stakeholders’ interests and ensuring the sustainability of the company long-term. In addition, CSR disclosure is considered to be an assertion of a company’s brand differentiation, which means obtaining operating licenses both from the government and society, and the company’s risk management strategy.